2008
DOI: 10.1080/00016350802139833
|View full text |Cite
|
Sign up to set email alerts
|

Influence of convergence angle and cement space on adaptation of zirconium dioxide ceramic copings

Abstract: Within the limitations of the present study, the internal spaces of zirconia ceramic copings may decrease as the convergence angles of abutments increase. The computer-fixed cement space might influence the marginal adaptation of zirconia ceramic copings. The internal and marginal adaptation of zirconia ceramic copings obtained was within the range of clinical acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 15 publications
8
56
1
Order By: Relevance
“…The adaptation of most zirconia-based restorations fabricated with CAD/CAM technology is within the acceptable range for meeting clinical requirements (13)(14)(15)(16)(17)(18). Some basic in vitro studies have evaluated the adaptation of single crown restorations in terms of clinical parameters for tooth preparation.…”
Section: Marginal and Internal Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation of most zirconia-based restorations fabricated with CAD/CAM technology is within the acceptable range for meeting clinical requirements (13)(14)(15)(16)(17)(18). Some basic in vitro studies have evaluated the adaptation of single crown restorations in terms of clinical parameters for tooth preparation.…”
Section: Marginal and Internal Adaptationmentioning
confidence: 99%
“…Increasing the convergence angles of the tooth abutments reportedly improved the internal (16) and marginal (17) adaptation of zirconia-based crowns. Using CAD software, Iwai et al (16) found that computer-fixed cement spaces with might influence the marginal adaptation of zirconia-based crowns.…”
Section: Marginal and Internal Adaptationmentioning
confidence: 99%
“…8 When using light microscopy directly, only the marginal gap width can be determined, 8 and when using a number of prepared teeth and then sectioning the crowns/teeth, the gap width could be influenced by such factors as the design of the prepared teeth. [25][26][27][28] It should be noted, however, that with the replica technique used in the present study the crowns were filled with light-body impression material and held in place with finger pressure. This could have resulted in a variable force applied on the crowns, but the experimental setup imitates the way crowns are usually placed in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the divergent gap width determined in the three studies could be that the there were slight differences in convergence angle and/or in the finishing margin design of the prepared teeth and/or differences in preparation depth. [25][26][27][28] Regarding the internal fit, internal discrepancies may weaken the ceramic crowns, so the marginal and internal fits are among the important criteria for the long-term success of ceramic restorations. For example, because the space between the tooth and the restoration exposes the luting material to the oral environment, a wide gap discrepancy may cause cement solubility, plaque accumulation, marginal leakage, and crown failures.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[6][7][8] Vertical gaps may be introduced during either fabrication step, including during computer-aided design (CAD)/ computer-aided manufacturing (CAM) digitization. 9 Hence, since both the scanning technique 7,9 and the preparation design [10][11][12] may play an important role in the clinical success of the denture, different preparation angles can be evaluated to test the accuracy of different CAD/CAM systems.…”
Section: Introductionmentioning
confidence: 99%